Local anharmonic effects in high-Tc superconductors. Pseudospin-electron model - Stasyuk, I.V. (Condensed Matter Physics, 1999)
Some aspects of physical phenomena in high-Tc crystals caused by anharmonicity of the crystal lattice are discussed. Appropriate theoretical models
are considered. A review is given of the results obtained while investigating
the pseudospin-electron model (PEM) when applied to the description of
structural and dielectric instabilities, phase separations and bistability phenomena. The theoretical problems are analyzed arising in PEM when the
strong short-range correlations and electron transfer are taken into account
simultaneously. В роботi обговорюються деякi аспекти фiзичних явищ у кристалах з
високотемпературною надпровiднiстю, зумовленi локальною ангармонiчнiстю їх кристалiчної гратки. Розглядаються вiдповiднi теоретичнi моделi. Дається огляд результатiв, отриманих при дослiдженнi псевдоспiн-електронної моделi при її застосуваннi до опису структурних i дiелектричних нестiйкостей, фазових розшарувань та явищ
бiстабiльностi. Аналiзуються теоретичнi проблеми, що виникають у
ПЕМ при одночасному врахуваннi сильних короткосяжних кореляцiй
та електронного переносу.